Connectivity and higher education in the context of the COVID-19 pandemic, perceptions by students of Public Universities (UNA - UCR - UNED - UTN) - Chanto Espinoza, Carlos Luis (2021)
This article explores the perceptions on connectivity in higher education in the context of the COVID-19 pandemic by students from four public universities in Costa Rica, Universidad Nacional (UNA), Universidad de Costa Rica (UCR), Universidad Estatal a Distancia (UNED) and Universidad Técnica Nacional (UTN). The results of a survey carried out on a sample of 302 active students of the aforementioned universities in the province of Guanacaste are presented through a quantitative, descriptive, non-experimental approach, using the questionnaire and literary review to compile the information. It is remarkable the results that affirm the impact caused and dependence on technology for educational practice in times of coronavirus where good connectivity can make a difference for good student performance. Finally, it is taken as fact the existence of low connectivity in the rural areas of Guanacaste, the existence of students without adequate technological equipment to perform in remote presence, added to the poor internet service by different providers, and the dependence on laptops and cell phones for programmed synchronous and asynchronous activities.